Insertion of a testicular prosthesis at the time of radical orchiectomy for testicular cancer is safe in patients who will subsequently undergo chemotherapy or radiotherapy. (30th April 2020) - Musi, Gennaro; Cozzi, Gabriele; Mistretta, Francesco Alessandro; Tringali, Valeria Maria Lucia; Serino, Alessandro; Jereczek‐Fossa, Barbara Alicja; Verri, Elena; Ferro, Matteo; Catellani, Michele; de Cobelli, Ottavio
Abstract: We aimed to assess the incidence of prosthesis‐related complications in patients who received a testicular prosthesis at the time of radical orchiectomy for testicular cancer and were then treated with chemotherapy (ChT) or radiotherapy (RT). We reviewed the records of the patients who underwent radical orchiectomy at our Institute since 1999; we also retrieved data from patients who underwent surgery elsewhere and then received ChT or RT at our Institution since 1999. We used the chi‐square test to evaluate differences in the incidence of prosthesis‐related complications between the groups. We retrieved the records of 587 patients; 393 had a testicular prosthesis implanted. Median follow‐up was 57.7 months. One hundred thirty‐eight patients (35.11%) received ChT, 129 RT (38.82%) and 10 (2.55%) both ChT and RT; of them, 6 (4.34%), 8 (6.20%) and 0 reported problems respectively. Seven (6.03%) of the 116 patients (29.52%) who had no further treatment had complications. The incidence of complications was not significantly different between patients who had no further treatment versus patients who underwent ChT ( p  = .75) or RT ( p  = .83). Testicular prosthesis insertion at the time of radical orchiectomy is safe even in patients subsequently undergoing ChT or RT.